MOTIF PENOLAKAN BANGLADESH TERHADAP PENGUNGSI ROHINGYA - Siti Aulia Nurjanah (HI 16 UMY 187, 2016)
*187 This study aims to determine the motive of the refusal of Bangladesh on Rohingya refugees that occurred in 2009 to 2012. This study uses literature study were taken from a number of books, journals, websites, and quantitative data as a supporter. This study uses Decision Making Theory by Richard C. Snyder. There are internal and external factors that underlie the rejection made by Bangladesh on Rohingya refugees. Internal factors underlying the refusal of Bangladesh to Rohingyas are first, limited capability Bangladesh to accommodate and provide a decent life for the Rohingya refugees. Second, the absence of binding legal requiring Bangladesh to accommodate refugees from anywhere, including the Rohingya. Third, Rohingya refugees pose many problems penalizing the government of Bangladesh. And the external factors that underlie the refusal of Bangladesh to Rohingyas are their direct assistance from UNHCR.